The playwriter Terence and his plays in Celestina comentada - González Vázquez , Carmen (Cuadernos de Filología Clásica. Estudios Latinos, 2024)
Celestina comentada represents the inaugural comprehensive commentary elucidating how La Celestina was read during the sixteenth century. The playwright Terence plays an important role in this work, as the author of the Commentary posits that specific passages of La Celestina contain allusions to verses from Terence's comedies. The purpose of this study is to identify and analyse the passages that allude to Terence and his comedies. This will enable us to ascertain the extent of Terence's influence, the reasons for it, and the value placed upon him by the author of Celestina comentada, also in the literary context of La Celestina itself.
Keywords: Terence; comedies; Celestina; Celestina comentada; sources